Effective microorganism pre-treatment on oil palm empty fruit bunch fibre for cultivation of Volvariella volvacea (Bull.) singer - Umor, N.A.; Abdullah, S.; Azhar, M.; Ismail, S.; Ismail, S.I.; Misran, A.; Mahmud, T.M.M. (Rynnye Lyan Resources, 2023)
Pre-treatment with effective microorganisms (EM) for the cultivation of Volvariella volvacea using oil palm empty fruit bunch (EFB) was proposed to increase yield. The effect of different EM doses on the mycelium growth and yield was observed. The treatment was carried out using a combination of two parameters: composting times (5 days (T1), 10 days (T2) and 15 days (T3) and dosages of EM (0% (E1), 10% (E2), 20% (E3) and 30% (E4). While the composition of EFB was analysed to compare the changes before and after the pre-treatments. It was determined that EM pre-treatments of 20% and 30% resulted in significantly faster mycelial growth compared to the other treatments. The highest yield of V. volvacea was observed at T2E4 (10d, 30% EM) with 271.5±57.28 g or biological efficiency (B.E) of 9.11%. The highest average weight per fruiting body (FB) was obtained at T1E3 (5d, 20% EM) with 14 g, while T2E4 (10d, 30% EM) yielded the highest number of harvested FB with 42. Cellulose, hemicellulose and lignin were reduced in all treatments tested. Both EM dosages and composting times significantly affected the yield of V. volvacea. EFB fibre was a potential substrate for the cultivation of V. volvacea.